Pengembangan Sistem Pelaporan Kerusakan Jalan Berbasis Android Untuk Daerah Kota Malang Menggunakan Konsep Crowdsource - Ardi Wicaksono; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the city of Malang, there are many traffic jams at many points, both on the protocol road and on the roads of the village. Apart from the fact that Malang City has a large population, the density of transportation or congestion that occurs is also caused by damage to the road. This is also a factor in the occurrence of traffic accidents on the highway. Damages to the road cannot be quickly handled by the Malang City government. This is because the city of Malang has a fairly large area of 110.6 square kilometers, and the survey process that must be carried out is quite time-consuming and costly. Difficulties are also experienced by people who want to report a road damage, including because they do not know the procedures that must be done to report. The Road Reporting System, offers a reporting mechanism, whereby the reporter can send his report anywhere in the city of Malang to the Binamarga official in Malang City, and the Malang City office will be easier to collect road damage data. The Road Reporting System consists of two applications, namely, a reporting application built on the Android platform for reporters, and an admin application built on the nodeJs web application platform for Malang City services.